Fatigue in fiber-metal laminates for small wind turbine blades application - Sai, Wei (2018)
A methodology to study the fatigue of a wind turbine blade in a 10KW small wind turbine is proposed in this paper. Two working conditions (namely normal fatigue operation condition and extreme wind condition) are considered based on IEC61400-2. The maximum load calculated from both cases were used as a reference to perform material sample fatigue study. Fiber-metal laminate – GLARE 3/2 with a centre 1mm notch on the external aluminium layers was modelled based on fracture mechanics approach to calculate the stress intensity factor and fatigue crack growth rate at maximum applied stress of 240Mpa. GLARE panel fabrication and tensile tests were included. The fatigue tests were performed on unnotched samples with stress range from 80Mpa to 300Mpa and plotted into S-N curve.